2018
DOI: 10.1302/2046-3758.74.bjr-2017-0245.r1
|View full text |Cite
|
Sign up to set email alerts
|

Global transcriptome analysis to identify critical genes involved in the pathology of osteoarthritis

Abstract: ObjectivesThe aim of this study was to identify key pathological genes in osteoarthritis (OA).MethodsWe searched and downloaded mRNA expression data from the Gene Expression Omnibus database to identify differentially expressed genes (DEGs) of joint synovial tissues from OA and normal individuals. Gene Ontology (GO) and Kyoto Encyclopaedia of Genes and Genomes (KEGG) pathway analyses were used to assess the function of identified DEGs. The protein-protein interaction (PPI) network and transcriptional factors (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 44 publications
1
20
0
Order By: Relevance
“…ADAMTS1 breaks aggrecan and versican and is expressed in cartilage and synovium. Data about its expression in OA are controversial; some authors reported an increased expression in cartilage [139] whereas recent results using qRT-PCR showed that ADAMTS1 is downregulated in joint synovial tissues [140].…”
Section: Aggrecanases and Proteoglycanasesmentioning
confidence: 99%
“…ADAMTS1 breaks aggrecan and versican and is expressed in cartilage and synovium. Data about its expression in OA are controversial; some authors reported an increased expression in cartilage [139] whereas recent results using qRT-PCR showed that ADAMTS1 is downregulated in joint synovial tissues [140].…”
Section: Aggrecanases and Proteoglycanasesmentioning
confidence: 99%
“…FK506 binding protein 5, encoded by the FKBP5 gene, belongs to the immunophilin protein family, which plays a key role in immunoregulation and cellular processes by affecting protein folding and transportation (Zhang et al, 2018). Researchers have found that the expression of FKBP5 is downregulated in the cartilage of OA (Thakur, Dawes, & Mcmahon, 2013).…”
Section: Roc Curve Analysismentioning
confidence: 99%
“…Youden's index was used to show the most diagnostic threshold for each gene. The area under curve (AUC) was used to evaluate the effectiveness of these genes as biomarkers of OA [22,23] .…”
Section: Receiver Operating Characteristic (Roc) Analysismentioning
confidence: 99%